HUMAN CAPITAL IN THE KNOWLEDGE ECONOMY - Vasily Y. Kalachev (Advanced Engineering Research)
Peculiar features of the knowledge economy are investigated. The author’s own view on the content of such categories as 'capital' and 'human capital' is given, the role of the latter in the knowledge economy is specified.